FRI0689 Lipid peroxidation as risk factor for endothelial dysfunction in antiphospholipid syndrome (APS) patients. (15th June 2017) - Stojanovich, L; Stanisavljevic, N; Djokovic, A; Zdravkovic, M
Abstract : Background: APS pathophysiology is not clear enough yet since it has been implicated that aPL can activate cells (endothelial cells, monocytes, platelets), interfere with hemostatic reactions and activate complement reactions [1, 2]. Objectives: The aim of this study was to evaluate oxidative stress markers and it relations to endothelial damage as risk factor for thrombosis in patients with primary (PAPS) and secondary (SAPS) antiphospholipid syndrome (APS) in correlation to traditional risk factors. Methods: Flow mediated (FMD) and nitroglycerine (NMD) induced dilation of the brachial artery were studied in 140 APS patients (90 PAPS, 50 SAPS) and 40 controls matched by age, sex and conventional risk factors for atherosclerosis. Markers of oxidative stress: lipid hydroperoxydes (LOOH), advanced oxidation protein products (AOPP), total sulfhydryl grups (tSHG) and paraoxonase 1 activity (PON1) were determined by spectrophotometric method. Results: Oxidative stress dominate in APS patients. LOOH and AOPP correlate to lipid fractions (p<0.05), unlike PON1, tSHG that correlated to antiphospholipid antibody positivity (p<0.05). FMD was lower in APS patients comparing to controls (p<0.001). Cholesterol is independent variable for FMD impairment in control group (p=0.011); LOOH in PAPS (p=0.004); LOOH, aCL and triglycerides in SAPS patients (p=0.009, p=0.049 and p=0.012, respectively).Combined predictive of aCL and LOOH is better for FMD impairment than LOOH alone in both PAPS and SAPS patients (AUC 0.727, p=0.001, 95% CI 0.616–0.837 and AUC 0.824, p<0.001, 95% CI 0.690–0.957, repectively). Conclusions: Endothelial dysfunction is doubtlessly present in APS patients with oxidative imbalance as additional risk factor among other risk factors for clinical event. Anticardiolipin antibodies affect endothelial dependent vasodilatation in SAPS patients. We demonstrated synergistic effect of aCL and LOOH as risk for endothelial impairment in both PAPS and SAPS patients. References: Foltyn Zadura A, Memon AA, Stojanovich L, Perricone C, Conti F, Valesini G et al (2015) Factor H Autoantibodies in Patients with Antiphospholipid Syndrome and Thrombosis. J Rheumatol 42(10):1786–93. Stalc M, Poredos P, Peternel P, Tomsic M, Sebestjen M, Kveder T (2006) Endothelial function is impaired in patients with primary antiphospholipid syndrome. Thromb Res 118:455–461. Becarevic M, Stojanovich L, Ignjatovic S, Dopsaj V. The IgM isotype of anti-annexin A5 antibodies and multiple positivity of conventional antiphospholipid antibodies: increasing the number of clinical manifestations of primary antiphospholipid syndrome. Clinical Rheumatology 03/2016; doi: 10.1007/s10067-016-3230–0. Ames PR, Batuca JR, Ciampa A, Iannaccone L, Delgado Alves J (2010) Clinical relevance of nitric oxide metabolites and nitrative stress in thrombotic primary antiphospholipid syndrome. J Rheumatol 37:2523–2530. Acknowledgements: This work was supported by research grant number 175041, and TR 32040 for 2011 - 2017, issued by the Ministry of Science of the Republic of Serbia. Disclosure of Interest: None declared